Análise espaço-temporal da cobertura vegetal e uso da terra na reserva extrativista Marinha Caeté-Taperaçu, Bragança/PA - LEÃO, Sheyla da Silva (2019)
Mangroves are the target of a series of threats that result in a decline in the supply of natural resources to traditional communities and sectors that survive. The Amazon Coast stands out as the largest continuous strip of mangrove in the world, one of the most significant areas of biological productivity in the country. In it is located the Marine Extractive Reserve of Caeté-Taperaçu, Federal Conservation Unit located in the coastal plain of Bragantina, Northeast of Pará, municipality of Bragança. This paper intends to evaluate the spatio-temporal changes in relation to the creation of the Conservation Unit mentioned. For this, a spatial-temporal analysis was carried out in order to identify, classify and compare the land use classes in the study area, considering LANDSAT images 5 and 8 of the years: 1986, 2005 and 2018, evaluating scenarios before, during and after its creation. The object-oriented classification method was used, determining six classes of use, which gave rise to thematic mapping. It is noticed that the dynamics in the environment of macromarés was the environmental factor that influenced the loss and gain in area in most of the land use classes identified. It was possible to infer that the extractive practices have not influenced in an expressive way the ecological processes in the RESEX area.